Potential Novel Food-Related and Biomedical Applications of Nanomaterials Combined with Bacteriocins - Atanu Naskar; Kwang-sun Kim (MDPI AG, 2021)
Bacteriocins are antimicrobial peptides or proteinaceous materials produced by bacteria against pathogens. These molecules have high efficiency and specificity and are equipped with many properties useful in food-related applications, such as food preservatives and additives, as well as biomedical applications, such as serving as alternatives to current antibacterial, antiviral, anticancer, and antibiofilm agents. Despite their advantages as alternative therapeutics over existing strategies, several limitations of bacteriocins, such as the high cost of isolation and purification, narrow spectrum of activity, low stability and solubility, and easy enzymatic degradation, need to be improved. Nanomaterials are promising agents in many biological applications. They are widely used in the conjugation or decoration of bacteriocins to augment the activity of bacteriocins or reduce problems related to their use in biomedical applications. Therefore, bacteriocins combined with nanomaterials have emerged as promising molecules that can be used in various biomedical applications. This review highlights the features of bacteriocins and their limitations in biomedical applications and provides a detailed overview of the uses of different nanomaterials in improving the limitations. Our review focuses on the potential applications of nanomaterials combined with bacteriocins as new designer molecules for use in future therapeutic strategies.